FACILITATIVE COMPETENCE OF FUTURE TEACHERS IN THE FIELD OF DEVICTIMIZATION of TEENAGERS - Оліфірович, Наталія Іванівна; Яценко, Тетяна Євгеніївна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article reveals the essence of devictimization as a new direction of professional activity of the modern teacher. The author’s classification of types of role-victim behavior of teenagers is given, which is subject to correction in the course of devictimization. The procedure of determining the composition facilitating competencies of future teachers is described. The results of the empirical study of the operational and value characteristics of facilitating competencies of future teachers in the field of devictimization of adolescents with instrumental and non-instrumental victim behavior are given. The conclusion is formulated about without knowing the future teachers holistic techniques of using of facilitating competencies, the dominance of the teacher in interaction with victim adolescent and maintaining the stability of their victim behavior as the guiding principle for the use of students of these competencies, a low level of awareness them of the intentional plan of the speech addressed to victim adolescents, and its devictimization effect